Chemical imaging of ambient aerosol particles: Observational constraints on mixing state parameterization. Issue 18 (28th September 2015) - O'Brien, Rachel E.; Wang, Bingbing; Laskin, Alexander; Riemer, Nicole; West, Matthew; Zhang, Qi; Sun, Yele; Yu, Xiao‐Ying; Alpert, Peter; Knopf, Daniel A.; Gilles, Mary K.; Moffet, Ryan C.
Abstract: A new parameterization for quantifying the mixing state of aerosol populations has been applied for the first time to samples of ambient particles analyzed using spectro‐microscopy techniques. Scanning transmission X‐ray microscopy/near edge X‐ray absorption fine structure (STXM/NEXAFS) and computer‐controlled scanning electron microscopy/energy dispersive X‐ray spectroscopy (CCSEM/EDX) were used to probe the composition of the organic and inorganic fraction of individual particles collected on 27 and 28 June during the 2010 Carbonaceous Aerosols and Radiative Effects study in the Central Valley, California. The first field site, T0, was located in downtown Sacramento, while T1 was located near the Sierra Nevada Mountains. Mass estimates of the aerosol particle components were used to calculate mixing state metrics, such as the particle‐specific diversity, bulk population diversity, and mixing state index, for each sample. The STXM data showed evidence of changes in the mixing state associated with a buildup of organic matter confirmed by collocated measurements, and the largest impact on the mixing state was due to an increase in soot dominant particles during this buildup. The mixing state from STXM was similar between T0 and T1, indicating that the increased organic fraction at T1 had a small effect on the mixing state of the population. The CCSEM/EDX analysis showed the presence of two types of particle populations: the first was dominated by aged sea‐salt particles and had a higher mixing state index (indicating a more homogeneous population); the second was dominated by carbonaceous particles and had a lower mixing state index. Key Points: Parameterization of imaged particles enables quantification of mixing state Two major mixing states were observed in Sacramento Mixing state parameterization is dependent on analytical technique